(untitled) (Journal of Partial Differential Equations, 1996)
The existence and nonexistence of interfaces of weak solutions for nonlinear degenerate parabolic systems ∂u_i∂t - div (|∇u|^p-2∇u_i) = 0, i = 1, 2, …, m with p > 1 are studied in this paper.